(untitled) (Praxis Educativa, 2020)
I analyze a national policy implemented in Argentina between 2007 and 2016 in the National Directorate of Socio-Educational Inclusion of the Ministry of Education of the Nation: the National Program of Educational Extension-Centers of Youth Activities (PNEE-CAJ). I make a characterization in relation to its background, its formulation and implementation and what remains after its recent disarticulation. I inquire into that evolution: the implementation of instruments, procedures, devices, non-explicit rules, values and interventions. I perform the interpretation based on interviews, participant observation and document analysis. I highlight the identification of continuities and transformations between the program and the device that I recognize as a direct antecedent. I also highlight the presence of different perspectives of inclusion involved in both. Finally, I recover as relevant for the imprint that the program took its formulation within that Directorate.